“A.I. is a distraction. The glory of language is in its ambiguity”: Narrating Contemporary Reality with Jeanette Winterson (Altre Modernità, 2024)
A conversation with Jeanette Winterson (8 July 2023) by Andrea Raso(Università degli Studi Roma Tre)